Deconstructing the male's perceptions on sexual harassment towards women wearing revealing clothes in the television - Delos Reyes, Ritzleen; Escano, Ma. Teresa R. (2019)
The researcher discussed and analyzed the different perceptions of male on sexual harassment towards women who wear revealing clothes in the television. The study focused on women on the longest-airing noontime variety shows in the Philippines which are the It?s Showtime! Of ABS-CBN, and Eat Bulaga! Of GMA. Due to rampancy of sexual harassment in the Philippine setting, the researcher has included the Philippine Media entertainment contents, portrayal of women in media, and women objectification in the literature so that readers would have a short backgrounder and understanding of the study. The study was conducted in Barangay Mintal, Davao City where the researcher interviewed 100 men aged 21-40 years old. The questions to the respondents during the interview included their socio-demographics, television viewing babits, and their sexual attitude scale. The researcher then categorized the results of the interview into three sections, the 1.) Positive perceptions, 2.) Negative Perceptions, and 3). Neutral Perceptions. Aside from categorizing the answers, the analyses of the study were also grounded to the Male Gaze theory, the answers were interpreted on how it supports of debunks the claims of the theory. The study has shown results that men in Barangay Mintal, Davao City have negative perceptions and comments towards women who wear revealing clothes in the television. The researcher then challenged media producers to be careful and give high regards to their media portrayals of women, and also suggests to the future communication and media researcher to create tools to help people in this community to change the negative perceptions towards women wearing revealing clothes and educate them properly about sexual harassment.